"Es herrschen Sitten und Gebräuche, genauso wie im 30-jährigen Krieg" das erste Jahr des deutsch-sowjetischen Krieges in den Dokumenten des Generals Gotthard Heinrici - Hürter, Johannes 1963- (Vierteljahrshefte für Zeitgeschichte, 2000)
The letters and diary entries of General Gotthard Heinrici, a representative selection of which are given here, reflect the mentality of a high ranking German officer and his perception of warfare during the first year of the German-Soviet war. They show the pressures of a war of unparalleled hardness placed upon a commanding officer of an army corps and later, of an entire army. They also manifest Heinrici's preoccupation with questions that went beyond the daily routine of military life. From the general's point of view a broad picture of this war is presented. The brutalization resulting from the battles against the Red Army and partisans are dealt with, as is the treatment of civilians. That a general, such as Heinrici, permitted himself to such ruthless conduct of war was not only based on National Socialist strictures or on-the-spot observations, but also, on political and military experiences going back much further. It would appear that the unchecked escalation of violence thus released seemed finally comparable only with the situation surrounding the Thirty Years' War. However, the norms of a "respectable war", which the military elite had developed over the centuries, were no longer valid. (Vierteljahrshefte für Zeitgeschichte / FUB)